Factors Affecting Profitability in Sharia Business Unit Banks in Indonesia for the 2018-2022 Period - Sari, Elindian Kartika; Ulya, Zikriatul (CV. Rayyan Dwi Bharata, 2024)
This study aims to look at the effect analysis of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses Operating Income (BOPO) on the profitability of Return On Assets (ROA) of Islamic Business Unit Banks in Indonesia. In this study using a quantitative approach to secondary data in the form of time series data period 2018-2022. The population of this study is a Sharia Business Unit Bank registered with the Financial Services Authority. The data analysis technique used is multiple linear regression, namely testing the effect of the independent variable (X) on the dependent variable (Y). The results of this study indicate that Non Performing Financing (NPF) has no positive effect on ROA profitability with a value of 0.17390.05. The Financing to Deposit Ratio (FDR) has a positive effect on ROA profitability with a value of 0.00000.05. And Operating Expenses Operating Income (BOPO) has a positive effect on ROA profitability with a value of 0.00000.05. The NPF variable partially has no effect on ROA, while the FDR variable and BOPO variable simultaneously have a significant effect on ROA in Islamic Business Unit Banks in Indonesia.